IMPLEMENTASI PASAL 40 AYAT (1) PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH TERKAIT PENDAFTARAN AKTA PEJABAT PEMBUAT AKTA TANAH (Studi di Kantor Pertanahan dan Kantor Notaris/PPAT Kabupaten Malang) - Zakiya Kusuma Wardhani; Isdiyana Kusuma Ayu; Pinastika Prajna Paramita (Dinamika, 2022)
ABSTRACT               Not later than 7 (seven) working days from the date of signing the deed in question, the land deed official is obligated to submit the deed he made along with the relevant documents to the Land Office for registration. What if this is not done by the land deed official or it is late due to negligence, then are there special sanctions against the land deed official in question. The problems discussed are (1) How is the implementation of Article 40 section (1) of Government Regulation No. 24 of 1997 concerning Land Registration by land deed official at the Office of the National Land Agency? (2) What are the legal consequences for land deed official if they do not carry out land registration in accordance with Article 40 section (1) of Government Regulation No. 24 of 1997 concerning Land Registration?The research method used in this research is empirical juridical, with a sociological juridical approach, while the data analysis is done descriptive-qualitatively. From the results of the research, it can be concluded that (1) the implementation of Article 40 section (1) of Government Regulation Number 24 of 1997 concerning Land Registration by land deed official at the Land Office (BPN), no one is on time to meet the deadline of 7 (seven) working days, such as which is mandated by Government Regulation Number 24 of 1997. (2) The legal consequence for land deed official if it does not register land in accordance with Article 40 section (1) Government Regulation Number 24 of 1997 concerning Land Registration, is in the form of a warning and an obligation to make a certificate or statement of delay.  Keywords: Implementation, Legal Consequences, Land deed official, Land Registration.  ABSTRAKSelambat-lambatnya 7 (tujuh) hari kerja sejak tanggal ditandatanganinya akta yang bersangkutan, PPAT wajib menyampaikan akta yang dibuatnya berikut dokumen-dokumen yang bersangkutan kepada Kantor Pertanahan untuk didaftar. Bagaimana jika hal tersebut tidak dilakukan oleh PPAT atau terlambat karena kelalaiannya, maka apakah ada sanksi khusus terhadap PPAT yang bersangkutan. Adapun masalah yang dibahas adalah (1) Bagaimana implementasi Pasal 40 ayat (1) Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah oleh PPAT di Kantor Badan Pertanahan Nasional? (2) Apa akibat hukumnya bagi PPAT apabila tidak melakukan pendaftaran tanah sesuai Pasal 40 ayat (1) Peraturan Pemerintah Nomor 24 Tahun 1997 tentang Pendaftaran Tanah ? Metode penelitian yang digunakan dalam penelitian ini adalah yuridis empiris dengan pendekatan yuridis sosiologis dan dianalisis secara deskriptif kualitatif. Dari hasil penelitian dapat disimpulkan bahwa (1) Implementasi Pasal 40 Ayat (1) Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah Oleh PPAT di Kantor Pertanahan/BPN, tidak ada yang tepat waktu memenuhi tenggat waktu selama 7 (tujuh) hari kerja, seperti yang diamanatkan oleh Peraturan Pemerintah Nomor 24 Tahun 1997. (2) Akibat hukumnya bagi PPAT apabila tidak melakukan pendaftaran tanah sesuai Pasal 40 Ayat (1) Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah, adalah berupa teguran dan kewajiban membuat surat keterangan atau surat pernyataan keterlambatan. Kata Kunci: Implementasi, Akibat Hukum, PPAT, Pendaftaran Tanah.